Populations of Odontesthes (Teleostei: Atheriniformes) in the Andean Region of Southern South America: body shape and hybrid individuals - Cussac, Victor Enrique (2015)
The Original distribution area of the Patagonian "pejerrey" Odontesthes hatcheri has been subjected in the last few decades to the introduction of a closely related species of "pejerrey"; the Bonaerensean Odontesthes bonariensis. ThisThis species currently coexists with O. hatcheri in some lakes and reservoirs, due to stocking practices, and new, uncertain taxonomic scenarios have been proposed sinceknowing that these twoboth species can interbreed and produce fertile hybrid offspring. Cytochrome b sequence analysis showed a high degree of genetic divergence (average 7%) between these two species and very low intraspecific variation in O. hatcheri. Geometric Morphometrics Analyses (GMA) used in this study detected shape differences in agreement with diagnostic characteristics of the each species. In one lake, putative hybrids exhibiting intermediate diagnostic characteristics, but O. hatcheri mtDNA haplotypes, were identified by GMA. Significant regressions between body shape, total phosphorus, and altitude were found, suggesting a certain level of dependence on trophic web structure. This multi-level approach strongly suggests the introgression of O. bonariensis genes into O. hatcheri populations throughout Patagonia. Similar situations have threatened biodiversity, indicating that invasions, non-native introductions and introgressive hybridization may have a negative impact on genetic resources available for aquaculture and fisheries, and may be major drivers for decline of native freshwater fish. Managers should take these risks into account when considering further exotic introductions.discriminated by Geometrics Morphometrics Analysis. Regarding the wide latitudinal range of the Patagonian pejerrey?s distribution and environmental heterogeneity, we searched for the relationship between body shape and environmental factors. Relationships were found between body shape and total phosphorus, coastline development, and altitude, which suggest a partial dependence of body shape on trophic web structure and habitat availability.